Landscape structure of the territory of the Povolzhsky section of the Nizhegorodskoe Povolzh'e National Park (Nizhny Novgorod Region, Russia) - Astashin Andrej; Vatina Ol'ga; Podkovyrina Valeriya; Ogurcov Aleksandr; Tihanov Evgenij (E3S Web of Conferences)
The authors have developed a scheme of landscape differentiation of the territory of the Povolzhsky section of the Nizhegorodskoe Povolzh'e National Park. Landscape differentiation of the territory was carried out on the basis of a thorough study of the territory during field work and analysis of stock data, which made it possible to identify not only types of landscapes, but also types of tracts. The paper gives a characteristic of each selected type of landscape and provides a list of the tracts, included in it. The spatial structure of landscapes and tracts is reflected on the corresponding maps, presented in the work. The researched territory is located at the southern boundary of the zone of mixed coniferous-deciduous forests and located on the over-floodplain terraces and floodplain of the left-bank part of the Volga River valley. The territory of the Povolzhsky section has high floristic and phytocenotic biodiversity, plant species, listed in the Red Book of Russia and the Nizhny Novgorod region have been preserved here, the points of finding of which are presented on the map of kinds of landscape, which allows us to establish the landscape conditionality of the spread of each plant species. To organize environmental and recreational work within the boundaries of the national park, a detailed scheme of the landscape structure of its territory is necessary, which was developed by the authors. During the research, 4 landscapes and a number of tracts were identified.